2017
DOI: 10.1080/08959420.2017.1328952
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of the Elderly Receiving Old Age Pension in Lesotho

Abstract: The southern African country of Lesotho introduced an old age pension scheme in 2004 with the aim of enhancing the quality of life (QoL) of the nation's elderly population. This study is the first to assess the physical, psychological, social, and environmental aspects of the health-related QoL of the elderly in Lesotho since the pension scheme was adopted. Data for this study were gathered using the World Health Organization QoL-BREF questionnaire. Mean QoL scores were compared across demographic, socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…Out of the 18 studies included, nine studies (50%) used a cross-sectional design [ 12 , 21 , 23 , 24 , 26 , 28 30 ] while eight studies (44%) performed a secondary data analysis of collected cross-sectional or longitudinal data [ 14 20 , 22 ] and one study (6%) used a longitudinal design [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 18 studies included, nine studies (50%) used a cross-sectional design [ 12 , 21 , 23 , 24 , 26 , 28 30 ] while eight studies (44%) performed a secondary data analysis of collected cross-sectional or longitudinal data [ 14 20 , 22 ] and one study (6%) used a longitudinal design [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“… Angola Cross sectional study • n = 1003 • 65.4% females • Age > 60 years Long-term care facilities SWLS 11 Van Biljon et al, 2015 [ 24 ] A partial validation of the WHOQOL-OLD in a sample of older people in South Africa South- Africa Cross sectional study • n = 176 • 71.6% female • Age > 60 years Long Term Facilities WHOQOL-OLD 12 Akosile et al, 2018 [ 25 ] Depression, functional disability and quality of life among Nigerian older adults: Prevalences and relationships. Nigeria Cross sectional study • n = 206 • 56.3% female • Age > 65 years Community WHOQOL-OLD 13 Mugomeri et al, 2017 [ 26 ] Quality of Life of the Elderly Receiving Old Age Pension in Lesotho. Lesotho Cross sectional study • n = 385 • Age > 70 years Community WHOQOL-BREF 14 Gureje et.al 2010 [ 27 ] Determinants of quality of life of elderly Nigerians: results from the Ibadan Study of Ageing Nigeria Longitudinal study • n = 2175 • Age > 65 years Community WHOQOL-BREF 15 Akosile et al, 2014 [ 28 ] Fear of Falling and Quality of Life of Apparently-Healthy Elderly Individuals from a Nigerian Population Nigeria Cross sectional study • n = 261 • 49.8% female • Age > 65 years Community SF-36 16 Ogunyemi et al, 2018 [ 29 ] Health-Related Quality of Life of the Elderly in Institutional Care and Non-Institutional Care in Southwestern Nigeria: A Comparative Study.…”
Section: Methodsmentioning
confidence: 99%
“…Unconditional cash transfers, such as old-age pensions, were also common, including in low- and middle-income countries (5, 198). Older women who received pensions had fewer missed meals (199), although evidence was mixed (200). In South Africa, granddaughters who cohabitated with women who received pensions had improved anthropometric measures and fewer missed meals, indicating spillover effects of pension transfers (199, 201).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…According to 8 studies providing figures on reliability, 5 instruments had a Cronbach's Alpha score of ≥0.7 (the SWLS (n = 3), the SF-12 (n = 1) and the WHOQOL-OLD (n = 1)), The study of Mugomeri et al [32], using the WHOQOL-BREF reported reliability of 0.68 and the study of Hamren et al [34] did not report on reliability of the full CASP-12 but on its subscales. Reliability of the subscales varied from 0.63 to 0.76.…”
Section: Reliability and Validity Of Instrumentsmentioning
confidence: 99%
“…In the remaining nine studies, the instruments were administered without need for translation, because either a translated form pre-existed or mode of administration was in English language. Lastly, in nine studies (using the WHOQOL, WHO-SAGE-INDEPTH, WHOQOL-OLD, SWLS, CASP-12 and EQ-6D) researchers removed or rephrase original phrases of the instruments and inserted statements that would be familiar to the population in question [14,22,21,30,31,32,33,34].…”
Section: Domains Time Investment and Possibility For Content Modifimentioning
confidence: 99%